The beach as an erogenous zone: figuring through painting - Coldicutt, Richard Phillip (Curtin University, 2014)
The feeling of tranquillity and freedom, so often associated with the zone that lies between dunes and breakers, belies vast complexities and subjectivities that regulate the littoral. The beach is a liminal place both physically and socially, a landscape of hypersensitivity existing in flux with an endlessly shifting environment ... an erogenous zone. This study, explores the complexities of this cultured space through a series of Acts performed and figured in both text and paint.